Mother to child transmission of the HIV: old concepts, new perspectives? - Sperb, Vicente (Brazilian Journal of Sexually Transmitted Diseases, 2017)
I read very carefully the interesting article by Barcellos et al. on human immunodeficiency virus (HIV) vertical transmission in the postnatal period through breastfeeding. The authors explained in a very elucidating and detailed way the cases of postnatal infection, as well as the clinical and epidemiological aspects. In this regard, we could look into a number of questions about HIV diagnosis, HIV pre and post-exposure prophylaxis, and antiretroviral adherence in women living with HIV(1). [...]